Anticancer potential of diarylidenyl piperidone derivatives, HO-4200 and H-4318, in cisplatin resistant primary ovarian cancer. Issue 10 (2nd October 2016) - ElNaggar, Adam C.; Saini, Uksha; Naidu, Shan; Wanner, Ross; Sudhakar, Millie; Fowler, John; Nagane, Masaki; Kuppusamy, Periannan; Cohn, David E.; Selvendiran, Karuppaiyah
ABSTRACT: We have previously developed a novel class of bi-functional compounds based on a diarylidenyl-piperidone (DAP) backbone conjugated to an N-hydroxypyrroline (-NOH; a nitroxide precursor) group capable of selectively inhibiting STAT3 activation, translocation, and DNA binding activity. HO-4200 and H-4318 are 2 such derivatives capable of inducing apoptosis in ovarian cancer cells through this mechanism and demonstrated efficacy in platinum resistant primary ovarian cancer cell populations and tumor tissues. The improved absorption and cellular uptake of HO-4200 by cancer cells was determined using optical and electron paramagnetic resonance spectrometry. Treatment of ovarian cancer cells with HO-4200 and H-4318 resulted in cleavage of caspase proteins 3, 7, and 9, as well as PARP and inhibition of the pro-survival protein, Bcl-xL, resulting in significantly decreased cell survival and increased apoptosis. HO-4200 and H-4318 significantly inhibit fatty acid synthase (FAS) and pSTAT3 and decreased the expression of STAT3 target proteins: Survivin, c-myc, Bcl-xl, Bcl-2, cyclin D1/D2, and VEGF were suppressed as analyzed using quantitative real time PCR. In addition, HO-4200 and H-4318 significantly inhibited migration/invasion, in primary ovarian cancer cell populations isolated from primary and recurrent ovarian cancer patients. Treatment of freshly collected human ovarian tumor sections with HO-4200 demonstrated significant suppression of pSTAT3 Tyr 705, angiogenesis (VEFG), and markers of proliferation (Ki-67) in ex vivo models. We have shown, for the first time, that the DAP compounds, HO-4200 and H-4318, inhibit cell migration/invasion and induce apoptosis by targeting FAS/STAT3 in human ovarian cancer cells, including primary ovarian cancer cell populations and tumor tissues. Therefore, our results highlight the clinical anti-cancer potential of HO-4200 and H-4318.